Correction: Improving the communication of multifactorial cancer risk assessment results for different audiences: a co-design process - Francisca Stutzin Donoso; Tim Carver; Lorenzo Ficorella; Nichola Fennell; Antonis C. Antoniou; Douglas F. Easton; Marc Tischkowitz; Fiona M. Walter; Juliet A. Usher-Smith; Stephanie Archer (Journal of Community Genetics, 2024)

Improving the communication of multifactorial cancer risk assessment results for different audiences: a co-design process - Francisca Stutzin Donoso; Tim Carver; Lorenzo Ficorella; Nichola Fennell; Antonis C. Antoniou; Douglas F. Easton; Marc Tischkowitz; Fiona M. Walter; Juliet A. Usher-Smith; Stephanie Archer (Journal of Community Genetics, 2024)
Background Multifactorial cancer risk prediction tools, such as CanRisk, are increasingly being incorporated into routine healthcare. Understanding risk information and communicating risk is challenging and healthcare professionals rely substantially on the outputs of risk prediction tools to communicate results. This work aimed to produce a new CanRisk report so users can directly access key information and communicate risk estimates effectively. Methods Over a 13-month period, we led an 8-step co-design process with patients, the public, and healthcare professionals. Steps comprised 1) think aloud testing of the original CanRisk report; 2) structured feedback on the original report; 3) literature review; 4) development of a new report prototype; 5) first round of structured feedback; 6) updating the new report prototype; 7) second round of structured feedback; and 8) finalising and publishing the new CanRisk report. Results We received 56 sets of feedback from 34 stakeholders. Overall, the original CanRisk report was not suitable for patients and the public. Building on the feedback, the new report has an overview of the information presented: section one summarises key information for individuals; sections two and three present information for healthcare professionals in different settings. New features also include explanatory text, definitions, graphs, keys and tables to support the interpretation of the information. Discussion This co-design experience shows the value of collaboration for the successful communication of complex health information. As a result, the new CanRisk report has the potential to better support shared decision-making processes about cancer risk management across clinical settings.

Optimal motor control may mask sensory dynamics - Sean G. Carver; Tim Kiemel; Noah J. Cowan; John J. Jeka (Biological Cybernetics, 2009)

Sensory reweighting with translational visual stimuli in young and elderly adults: the role of state-dependent noise - John Jeka; Leslie Allison; Mark Saffer; Yuanfen Zhang; Sean Carver; Tim Kiemel (Experimental Brain Research, 2006)

Modeling the Dynamics of Sensory Reweighting - Sean Carver; Tim Kiemel; John J. Jeka (Biological Cybernetics, 2006)

Comparing internal models of the dynamics of the visual environment - Sean Carver; Tim Kiemel; Herman van der Kooij; John J. Jeka (Biological Cybernetics, 2005)

Rapid pregermination and germination responses of Erysiphe pisi conidia to contact and light - Keiko Fujita; Alison J. Wright; Akane Meguro; Hitoshi Kunoh; Tim L.W. Carver (Journal of General Plant Pathology, 2004)

Changes in apoplastic antioxidants induced by powdery mildew attack in oat genotypes with race non-specific resistance - Hélène Vanacker; Christine H. Foyer; Tim L. W. Carver (Planta, 1999)